Konsep Kurikulum Merdeka Belajar Ditinjau dari Pandangan Aliran Filsafat Pendidikan Progresivisme - Norma Yunaini; Nurulhuda Md Hassan; Agus Kichi Hermansyah; Rukiyati Rukiyati; Mulyo Prabowo (JIP Jurnal Ilmiah PGMI, 2022)
This study examines the concept of independent learning from the perspective of progressivism educational philosophy. The method used in this research is library research. The researcher reviewed various works of literature and then analyzed related to the Concept of Merdeka Belajar Curriculum in Elementary Schools from the Viewpoint of Educational Philosophy. Data collection techniques are conducted by including eligibility, screening, identification, and analysis from various sources such as books, articles, and relevant research results. The search for research data resulted in 5 electronic books and 36 articles from scholars. The texts studied included educational philosophy books and independent curriculum guides specific to elementary schools. In contrast, there are several selected articles. Articles found in the Sholer and Mendeley databases, using the search terms "Independent Curriculum in elementary schools, Educational Philosophy, Progressivism" in the title and keywords only selected articles which are continued in the discussion and the papers used are the last five years published in national journals (Sinta 1, 2, 3, 4, 5) and several in international journals. Library materials from various sources, both in print and electronic form, go through the stages of eligibility, screening, identification, and analysis as needed to obtain proportions and ideas. The results of this study indicate the concept of independent learning with the flow of progressivism believes that education must be progressive, innovative, flexible, open, rational, and scientific according to the times. The concept of an independent learning curriculum in elementary schools from the point of view of the philosophy of progressivism education has similarities to progress and independence in educational practice. The relationship between the concept of independent learning in elementary schools from a progressivism point of view can be seen from the impact of its implementation: 1) for educators, the administrative burden will be reduced because the RPP tools are simplified; teachers have free time to improve competence through various platforms; Educators have the freedom to innovate and be creative. 2) Students can experience knowledge in their environment as character strengthening, learning themes, or critical issues related to sustainable lifestyles, culture, entrepreneurship, and technology. So that students can take real action in answering these issues according to the stages of learning and their needs.